Winter prey selection and estimation of wolf kill rates in Yellowstone National Park, 1995-2000 - Smith, Douglas W.; Drummer, Thomas D.; Murphy, Kerry M.; Guernsey, Debra S.; Evans, Shaney B. (Digital Commons @ Michigan Tech, 2004)
Wolf (Canis lupus) impacts on prey are a central post-wolf-reintroduction issue in the greater Yellowstone ecosystem (GYE) of the western United States. Further, estimates of wolf kill rates, used to understand these impacts, can be biased due to unrecovered kills. In Yellowstone National Park (YNP), visibility of wolves allowed us to combine independent aerial and ground observations and use a double-count method to estimate the probability of recovering kills. We consequently used these data to adjust estimates of wolf kill rates. We conducted monitoring annually from 1995 to 2000 during 2 30-clay periods in early (15 Nov-14 Dec) and late winter (Mar). Estimated recovery rates of wolf kills for ground and aerial crews were 50% and 45%, respectively, although we determined that this varied by location (distance from road) and possibly age (calf or adult) of the kill. The estimated combined recovery rate was 73%. Estimated wolf kill rates were higher in late winter (2.2 kills/wolf/month) compared to early winter (1.6 kills/wolf/month), with an overall estimated rate of 1.9 kills/wolf/month. The primary prey of wolves in winter was elk (Cervus elaphus; 90%). During our study, 43% of the elk killed were calves, 28% were adult females (cows), 21% were adult males (bulls), and 9% were of unknown age/sex. Comparing prey selection to prey availability, wolf packs residing on the northern range (NR) of the GYE selected for calves, against cows, and approximately proportional to availability for bulls. Prey use was different for wolf packs occupying the NR compared to packs residing in other areas (non-northern range [NNR]) and varied seasonally for NR packs. Variation in wolf kill rates by season, and the relative stability of the northern Yellowstone elk herd during a series of mild winters despite increases in wolf density, suggest that kill rates and ultimately elk population size are influenced by winter weather. Management of ungulates should reflect the addition of wolves combined with the unpredictability of ...